2021
DOI: 10.3390/molecules26102933
|View full text |Cite
|
Sign up to set email alerts
|

Ageratum conyzoides L. and Its Secondary Metabolites in the Management of Different Fungal Pathogens

Abstract: Ageratum conyzoides L. (Family—Asteraceae) is an annual aromatic invasive herb, mainly distributed over the tropical and subtropical regions of the world. It owns a reputed history of indigenous remedial uses, including as a wound dressing, an antimicrobial, and mouthwash as well as in treatment of dysentery, diarrhea, skin diseases, etc. In this review, the core idea is to present the antifungal potential of the selected medicinal plant and its secondary metabolites against different fungal pathogens. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 102 publications
0
23
0
1
Order By: Relevance
“…Remarkably, these compounds can also interfere with the competent discharge of mycotoxins in combination. Previous studies demonstrated that precocene II exhibited its activity by stopping the release of mycotoxins as aflatoxins and trichothecenes [56]. Wu et al showed that the fraction containing polymethoxyflavones from Citrus reticulata suppressed Aspergillus niger by altering the permeability of the cytomembrane and impairing the integrity of cell walls via inhibition of chitin production [52].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, these compounds can also interfere with the competent discharge of mycotoxins in combination. Previous studies demonstrated that precocene II exhibited its activity by stopping the release of mycotoxins as aflatoxins and trichothecenes [56]. Wu et al showed that the fraction containing polymethoxyflavones from Citrus reticulata suppressed Aspergillus niger by altering the permeability of the cytomembrane and impairing the integrity of cell walls via inhibition of chitin production [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some substances depending upon the situation and their chemical composition, behave as antioxidants or pro-oxidants, although there are many antioxidants with varying roles. It is important to note that two antioxidants showing the same effect cannot be replaced by one another as each has its biological significance (Chen et al 2018;Chahal et al 2021). Moreover, uptake of supplements via the mouth or by administering them directly in blood has a different impact.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Bioactive secondary metabolites, such as flavonoids, terpenoids, alkaloids, tannins, and others, have been recognized as potential medical resources [ 89 , 90 ]. As shown in Section 3 and Section 4 , AMG has high cytotoxicity.…”
Section: Nanotechnology Of Amg In Breast Cancermentioning
confidence: 99%